A fossil brain from the Cretaceous of European Russia and avian sensory evolution - Kurochkin, Evgeny N (The Royal Society, 2007)
Fossils preserving traces of soft anatomy are rare in the fossil record; even rarer is evidence bearing on the size and shape of sense organs that provide us with insights into mode of life. Here, we describe unique fossil preservation of an avian brain from the Volgograd region of European Russia. The brain of this Melovatka bird is similar in shape and morphology to those of known fossil ornithurines (the lineage that includes living birds), such as the marine diving birds Hesperornis and Enaliornis, but documents a new stage in avian sensory evolution: acute nocturnal vision coupled with well-developed hearing and smell, developed by the Late Cretaceous (ca 90 Myr ago). This fossil also provides insights into previous ‘bird-like’ brain reconstructions for the most basal avian Archaeopteryx—reduction of olfactory lobes (sense of smell) and enlargement of the hindbrain (cerebellum) occurred subsequent to Archaeopteryx in avian evolution, closer to the ornithurine lineage that comprises living birds. The Melovatka bird also suggests that brain enlargement in early avians was not correlated with the evolution of powered flight.